Pengaruh Kepemimpinan dan Motivasi terhadap Kinerja Karyawan di PT. BPR Siliwangi Tasikmalaya - Dhini Nurislami; Arga Sutrisna; Suci Putri Lestari (CV. Ulil Albab Corp, 2023)
This study aims to determine the effect of leadership and work motivation on employee performance at PT. BPR Siliwangi Tasikmalaya. The research method used is descriptive and associative method. The research population is the employees of PT. BPR Siliwangi Tasikmalaya with 51 employees. The sample in this study amounted to 51 employees and used a saturated sample. Data collection was carried out through distributing questionnaires. The data analysis technique used is descriptive analysis and multiple linear regression analysis. The results of this study show that simultaneously and partially, leadership and motivation each have a positive and significant effect on employee performance. Overall, leadership and motivation have a significant effect on employee performance at PT. BPR Siliwangi Tasikmalaya.This study aims to determine the effect of leadership and work motivation on employee performance at PT. BPR Siliwangi Tasikmalaya. The research method used is descriptive and associative method. The research population is the employees of PT. BPR Siliwangi Tasikmalaya with 51 employees. The sample in this study amounted to 51 employees and used a saturated sample. Data collection was carried out through distributing questionnaires. The data analysis technique used is descriptive analysis and multiple linear regression analysis. The results of this study show that simultaneously and partially, leadership and motivation each have a positive and significant effect on employee performance. Overall, leadership and motivation have a significant effect on employee performance at PT. BPR Siliwangi Tasikmalaya.